EFFECT OF QUALITY OF SERVICE ON CUSTOMER SATISFACTION ON GALAXY MART MANADO - FANDA OLIVIA BEATRICE SEGE; Tinneke M. Tumbel; Olivia Walangitan (JURNAL ADMINISTRASI BISNIS, 2017)
Retail business spread across the country is experiencing rapid development. Thisdevelopment is due to retail customers who prefer to buy different items in one place. Of themany marketing activities, supermarkets, mini markets and department stores compete to offera variety of shopping facilities ranging from services provided, discounts, payment options,and other facilities to create a sense of satisfaction for customers in shopping. The mainproblem in this research is "What Quality of Service Affects Galaxy Mart CustomerSatisfaction?". This study aims to determine whether the quality of service Galaxy Martinfluence on customer satisfaction. Talking about quality and customer satisfaction iscertainly closely related to marketing. The essence of marketing is to identify and meet theneeds and desires of consumers according to Kotler dan Keller (2016:27) â€œmarketing ismeeting needs profitabilityâ€ . Similar to retail, it can be understood as all activities involved inthe sale of goods or services directly to the end consumer for personal use rather thanbusiness use.This research type is quantitative research with technique of data analysis byusing interval scale research instrument, validity and reliability test, simple linear regressionequation and hypothesis test. Based on the results of research the influence of QualityCelebration is a variable that does not affect consumer satisfaction Galaxy Mart Supermarket.Based on the results of research hypothesis testing research states that the hypothesis isrejected because the influence of service quality has no effect on customer satisfaction. Then itcan be concluded that Service Quality does not significantly influence Customer Satisfactionthat if performance is below expectations, customer is not satisfied. If its performance meetsthe expectations of satisfied customers. If performance exceeds expectations, customers arevery satisfied or happy. In this case the company should further improve the Quality of Serviceto Customer Satisfaction, because customer satisfaction is very impactful for the company.Keywords: Service Quality, Customer Satisfaction